Analysis of High-Power Radar Propagation Environments Around the Test Site - Jongho Keun; Taekyeong Jin; Jeonghee Jin; Hosung Choo (Applied Sciences, 2025)
In this paper, we propose a novel evaluation method to assess the strength of electromagnetic (EM) waves in a specific area by analyzing the propagation environment at a radar testing site. To analyze the propagation environment of the radar test site, this evaluation method performs precise modeling of actual structures such as buildings and terrain. The calculated received power is then converted into electric field strength to compare with the reference threshold level (61 V/m). The electric field during the radar operation is examined by changing two scenarios: one is when the transmitter (Tx.) is directed toward the receiver (Rx.), and the other is when the Tx. is misaligned. In particular, it may increase the electric field strength near the Tx. system when Tx. and Rx. are misaligned. To reduce the impact of EM waves, we conducted a comparison based on the installation of absorbers. The results indicate that the received electric field shows attenuation rates of 39.47% in the X-band and 39.35% in the Ku-band, achieved with a 1 m absorber. In addition, the theoretical and average measured received powers of −61.9 dBm and −62.03 dBm, respectively, show good agreement with the simulated result of −64.64 dBm. This measurement procedure exhibits high accuracy when compared with theoretical and simulation results. These results demonstrate the reliability of the propagation environment analysis using the proposed integrated simulation model.